Design of a rotor blade tip for the investigation of dynamic stall in the transonic wind tunnel Göttingen - Lütke, B.; Neumann, J.; Schmidt, M. (My University, 2014)
The design of a pitching blade tip wind tunnel model with a double swept planform is presented. The geometry of the model and the experimental setup for the investigation of dynamic stall are shown. Steady and unsteady RANS calculations are performed to study the expected flow phenomena and identify the relevant loads at Ma = 0:4 and Re = 1:2 - 1:6 ? 106. First unsteady dynamic stall cases reveal no significant aerodynamic pitching moments. Design features of the highly loaded carbon fiber structure are presented. Different finite element (FE) modeling approaches for the carbon composite shells bonded to a steel shaft and a spar are described in detail. Eigenfrequencies, deformation and stress distribution are evaluated. Steady coupled simulations with different spar cap orientations reveal a slightly higher negative elastic twist for forward orientated carbon fibers.